Corrigendum: Comparative genomics of the Natural Killer Complex in carnivores - Futas, Jan; Jelinek, April L; Burger, Pamela A; Horin, Petr (Frontiers in immunology, 2024)
[This corrects the article DOI: 10.3389/fimmu.2024.1459122.].
Keywords: genomes; Natural Killer Complex; KLR; carnivore; Felids; CLEC